Pengaruh Profesionalisme, Kemampuan Manajerial Serta Kerjasama Tim Terhadap Kinerja Karyawan Pada PT Sucofindo Padang - Tiwi Novita Dewi; Lasti Yossi Hastini (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the influence of professionalism, managerial ability, and teamwork on employee performance at PT Sucofindo Padang. Employee performance is a crucial factor in determining organizational success, especially in the inspection, testing, and certification service industry. Factors such as professionalism, effective leadership, and teamwork are believed to play a significant role in improving productivity and service quality.This research employs a quantitative approach using explanatory research methods. The sample consists of 99 employees selected through purposive sampling. Data collection was conducted through questionnaires, while data analysis utilized multiple linear regression tests with the assistance of statistical software.The results indicate that professionalism, managerial ability, and teamwork have a positive and significant impact on employee performance both partially and simultaneously. Professionalism enhances work efficiency and accuracy, managerial ability influences leadership effectiveness and decision-making, while teamwork strengthens employee synergy in achieving organizational goals.This study contributes to human resource management by emphasizing the importance of strengthening professionalism, leadership, and teamwork as strategies for improving employee performance. The practical implications of this research can serve as recommendations for PT Sucofindo Padang in developing more effective training programs and HR policies.